How Employers in Poznań Agglomeration Perceive the Competences of Foreign Workers - Shelest-Szumilas, Olena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To assess the extent to which migrant workers employed by Polish companies adjust their skills to fit their employers’ needs. The study examines employers’ opinions about the competences of foreign workers employed in the Poznań area. Research Design & Methods: The data were collected with a survey and subjected to statistical analysis. Descriptive statistics and mathematical statistical methods were applied and presented. This is followed by a discussion of the results of previous empirical research in which foreign nationals self-assessed the match between their skills and the jobs they perform. Findings: Although a significant percentage of foreigners working in Poland are equipped with a high level of human capital, it is barely utilised by Polish enterprises. Implications / Recommendations: The employers do not recognise much of a skills mismatch. And even if they are aware of one, they are primarily shoring up their shorthanded workforce, not looking at the potential that could be utilized. The problem of skills mismatch among foreigner workers is exacerbated by Poland’s relative failure to exercise an integration policy. Contribution: The article argues for the need to undertake further in-depth research on the skills mismatch of foreign workers in Poland.